A community-level study on COVID-19 transmission and policy interventions in Wuhan, China. (August 2022) - Gao, Zhe; Wang, Siqin; Gu, Jiang; Gu, Chaolin; Liu, Regina
Abstract: The specific factors and response strategies that affect COVID-19 transmission in local communities remain under-explored in the current literature due to a lack of data. Based on primary COVID-19 data collected at the community level in Wuhan, China, our study contributes a community-level investigation on COVID-19 transmission and response strategies by addressing two research questions: 1) What community factors are associated with viral transmission? and 2) What are the key mechanisms behind policy interventions towards controlling viral transmission within local communities? We conducted two sets of analyses to address these two questions—quantitative analyses of the relationship between community factors and viral transmission and qualitative analyses of policy interventions on community transmission. Our findings show that the viral spread in local communities is irrelevant to the built environment of a community and its socioeconomic position but is related to its demographic composition. Specifically, groups under the age of 18 play an important role in viral transmission. Moreover, a series of community shutdown management initiatives (e.g., group buying, delivering supplies, and self-reporting of health conditions) play an important role in curbing viral transmission at the local level that can be applied to other geographic contexts. Highlights: It contributes a community-level study of viral transmission in Wuhan based on the primary COVID-19 data. Local viral transmission is observed to be only associated with the demographic composition of communities. The mobility of young population plays a key role in accelerating the virus transmission locally. Three effective mechanisms of curbing viral transmission are proposed.